APPLICATION OF TOOLS OF THE MONETARY POLICY ON ISLAMIC BANKS IN MALAYSIA - Ghandour, Ghassan Farouk (International Journal of Research -GRANTHAALAYAH, 2017)
Monetary policy should be reformulated in a way that is in line with Islamic banking by studying monetary policy tools and their primary and intermediate objectives, which are used for conventional banks to reach final objectives, to know their applicability to Islamic banks, New monetary policy tools that are compatible with the principles of Islamic banking and are capable of achieving two sets of objectives: The objectives of the final monetary policy determined by the monetary authority and choose to achieve rings of primary and intermediate objectives, and be linked to these tools that arm the monetary authority. The objectives of Islamic banks, namely to preserve their capital and maximize their profits, by attracting savings and developing them, and investing them in the legally permissible fields in all sectors of agriculture, industry, trade and services, and providing all banking services with an Islamic template.